Kenakalan Remaja : Faktor Penyebab, Dampak Dan Upaya - Avanza Fahlevi Zein; Uli Makmun Hasibuan; Mawaddah Ramadhani; Syifa Thahira (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Juvenile delinquency is a dynamic social phenomenon that demands serious attention. This qualitative study aims to examine the causal factors, impacts, and effective preventive measures regarding juvenile delinquency. The findings indicate that juvenile delinquency is driven by three main factors: family (improper parenting and lack of attention), environment (negative peer influence and socio-economic conditions), and the individual (low self-control and emotional instability). The negative impacts of this phenomenon affect not only the perpetrators but also families, schools, and society both psychologically and socially. This study concludes that addressing juvenile delinquency requires a holistic and collaborative approach among families, educational institutions, communities, and the government. Early intervention through moral reinforcement, social skills development, and character building is considered the most effective strategy to reduce delinquency rates.